2009
DOI: 10.1192/apt.bp.107.004309
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy: time to communicate

Abstract: SummaryThis article offers an introduction to advocacy on behalf of people with mental disorders and/or intellectual disabilities. It concentrates mainly on the issues related to independent specialist advocacy, but refers to other forms also. The term is itself contentious, having different meanings in different contexts. Some of these controversies are outlined here. Inevitably, diverse interpretations imply varying practices, and these too are illustrated briefly. Legislation and concordance of expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Advocates can be viewed as ‘pushy and aggressive’ (Fereday et al . ), considered ‘trouble makers’ by some health professionals (Carver & Morrison ) and other service staff who may perceive their views as criticism (Harrison & David ). Such conflict can place support worker advocates in vulnerable positions with their employing organisations (Jorgensen et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advocates can be viewed as ‘pushy and aggressive’ (Fereday et al . ), considered ‘trouble makers’ by some health professionals (Carver & Morrison ) and other service staff who may perceive their views as criticism (Harrison & David ). Such conflict can place support worker advocates in vulnerable positions with their employing organisations (Jorgensen et al .…”
Section: Discussionmentioning
confidence: 99%
“…). While self‐advocacy may be considered preferable, many people with ID require supportive advocacy to have their voices heard and their health rights met (Llewellyn & Northway ; Harrison & David ). Many factors influence the capacity of people with ID to engage in self‐advocacy, including communication difficulties (Reinders ; Ziviani et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). It also educates the person with intellectual disability and their supporter(s), ideally helping them to become stronger advocates for their own health‐related needs through better information and empowerment (Llewellyn & Northway ; Harrison & Davis ; Wullink et al . ).…”
Section: Support For Primary Health Carementioning
confidence: 99%
“…Improved health advocacy may be one way to diminish this barrier and ultimately improve the health of people with an intellectual disability. The central tenet of advocacy in health care is that service users should be enabled to speak up on their own behalf and empowered to take a lead in the decision‐making process (Harrison & Davis ). However, a review on autonomy in relation to health among people with intellectual disability found, in spite of decades of promoting inclusion, self‐determination and independence, autonomy in relation to health care has rarely been investigated in the literature (Wullink et al .…”
Section: Introductionmentioning
confidence: 99%